Characterization of lead-free bismuth titanate (Bi4Ti 3O12) synthesized by a modified oxalate co-precipitation method - Pusit Pookmanee (2018)
Bismuth titanate (Bi4Ti3O12) powders and ceramics were synthesized by a modified oxalate co-precipitation method, from the starting precursors of bismuth nitrate pentahydrate and titanium (IV) isoproproxide in the mole ratio of Bi: Ti of 4 : 3. The mill-precipitated powder was calcined at 500-800 °C for 2 h. The phase transition was studied by an X-ray diffractometer. An orthorhombic structure was obtained after calcination at 700 °C for 2 h. The morphology was characterized by a scanning electron microscope. The average particle size increased as the calcination temperature increased. Powder calcined at 700 °C for 2 h was pressed into pellets. The pellets were sintered at 900 and 1000 °C for 2 h. The phase and microstructure of the ceramic in the pellets were investigated by an X-ray diffractometer and a scanning electron microscope. A single phase orthorhombic structure of bismuth titanate was obtained. The average particle size increased as the sintering temperature increased. The chemical composition of the ceramics was analyzed by an energy dispersive X-ray spectrometer (EDXS). The elemental composition of bismuth, titanium and oxygen showed the characteristic X-ray energy values.